(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with the main principles of waste management in Ukraine, analyzes the current state and existing problems of utilization and recycling of wastes, proposes directions for their solution, identifies the deficiencies of the legislative base, organizational and information structure in the field of waste management, highlights the main aspects of the National Strategy waste management and the consequences of its approval in Ukraine, evaluation of European practice in this field and the possibility of its implementation in our country, it is proved that eco tech safety, including proper disposal of waste is part of the economic development. It has been determined that in order to create a successful management system in the field of waste management, it is necessary to reform not only the legislative base but also the organizational structure, but to reduce the risk of a negative impact on the health of the population and the environment is needed in the initial stages, based on the principles of hierarchy and Neighborhood It was found that improvement of the current state of waste management can be achieved by minimizing already existing waste and optimizing the possibilities of further processing, recycling for new wastes. It is also decided to include mining, chemical, metallurgical, machine-building, fuel and energy, construction, as well as agro-industrial complex enterprises in the main sources of waste generation. It is noted that the lack of technical possibilities for the reprocessing or disposal of certain types of waste is a prerequisite for the occurrence of uncontrolled emissions and utilization. In the end, the main directions for improving the current situation were to increase the amount and improve the quality of waste collection and to create waste recovery facilities, their recovery and utilization as soon as possible, in accordance with the latest technical standards.